2009
DOI: 10.1002/ps.1846
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reduced risk pesticides for use in greenhouse vegetable production on Bombus impatiens (Hymenoptera: Apidae)

Abstract: We conclude that the new reduced risk insecticides metaflumizone and chlorantraniliprole and the fungicides myclobutanil, potassium bicarbonate and cyprodinil + fludioxonil are safe for greenhouse use in the presence of bumble bees. This information can be used preserve greenhouse pollination programs while maintaining acceptable pest management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 14 publications
2
59
0
2
Order By: Relevance
“…Repeatability of metabolic rate (resting and recovery from exercise in fish) has also been shown to gradually decline over time (Norin and Malte, 2011), and a recent study suggested that this may be a general tendency (White et al, 2013). Metabolic phenotype during locomotion in bumblebees is probably relatively stable in adult life stage, averaging 60 days in workers of this species (Gradish et al, 2010), similar to recent observations on another flying insect (Niitepõld and Hanski, 2013). Nevertheless, transitions during maturation (Skandalis et al, 2011) and possibly senescence can affect repeatability estimates.…”
Section: Repeatability Of Flight Metabolic Rate and Wingbeat Frequencysupporting
confidence: 74%
“…Repeatability of metabolic rate (resting and recovery from exercise in fish) has also been shown to gradually decline over time (Norin and Malte, 2011), and a recent study suggested that this may be a general tendency (White et al, 2013). Metabolic phenotype during locomotion in bumblebees is probably relatively stable in adult life stage, averaging 60 days in workers of this species (Gradish et al, 2010), similar to recent observations on another flying insect (Niitepõld and Hanski, 2013). Nevertheless, transitions during maturation (Skandalis et al, 2011) and possibly senescence can affect repeatability estimates.…”
Section: Repeatability Of Flight Metabolic Rate and Wingbeat Frequencysupporting
confidence: 74%
“…In addition, chlorantraniliprole has exhibited activity against whitefly populations (Homoptera: Aleyrodidae) in laboratory and in the field as well as suppression of transmission of the begomovirus TYLCV Schuster et al 2008). Chlorantraniliprole also has shown safety to non-target arthropods, including pollinators, parasitoids and predatory insects and mites, and synergistic effects with an entomopathogenic nematode for controlling white grubs (Dinter et al 2008;DuPont 2008;Koppenhöfer & Fuzy 2008;Preetha et al 2009;Brugger et al 2010;Shaw & Wallis 2010;Gradish et al 2010Gradish et al , 2011. Thus, chlorantraniliprole is a promising tool as part of an integrated pest management program for B. tabaci, particularly where whiteflies have already developed resistance to other insecticide groups (Cahill et al 1996a, b, c;Palumbo et al 2001;Toscano et al 2001;Li et al 2003;Horowitz et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Insecticides in this class bind to and activate the ryanodine receptors in insect muscle cells, stimulating calcium release from the internal stores and causing impaired regulation, paralysis and death (Lahm et al 2005(Lahm et al 2009Cordova et al 2006Cordova et al , 2007Legocki et al 2008;Wilks et al 2008). Chlorantraniliprole has demonstrated efficacy in the field against biotype B of B. tabaci, especially when applied to the root zone Schuster et al 2008), and has been shown to be safe to non-target arthropods, including pollinators, numerous beneficial insects and predatory mites (Dinter et al 2008;DuPont 2008;Preetha et al 2009;Brugger et al 2010;Shaw & Wallis 2010;Gradish et al 2010Gradish et al , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…The low acute mortality caused by azadirachtin and chlorantraniliprole was expected, because the former usually requires very high doses to achieve repellence and impair development in Hymenoptera, 31 and the latter exhibits insecticidal activity limited to caterpillars, flies and beetles, 32,33 with low toxicity against honeybees and bumblebees at the recommended field label rate. 34,35 The differential ryanodine receptor sensitivity to chlorantraniliprole in bee pollinators is the likely reason for the low acute toxicity of this insecticide to bee species, 33,36 whereas the reasons for the low azadirachtin acute toxicity to pollinators have not yet been studied.…”
Section: Flight Take-off Activitymentioning
confidence: 99%